Effects of rigid and kinesio taping on plantar pressure distribution in patients with Lisfranc fracture sequelae. - ÖZEN BERKOL, TUĞÇE; KURU ÇOLAK, TUĞBA; POLAT, MİNE GÜLDEN (My University, 2023)
Background: Patients with Lisfranc fractures may regain functional status after anatomical fixation, but they may experience sequelae such as flatfoot deformity and pain associated with foot pressure distribution during weightbearing. Research question:: What is the impact of Lisfranc fracture sequelae on both the injured and uninjured sides, and how does the antipronation taping affect plantar pressure distribution parameters? Methods: Twenty-six patients who underwent anatomical fixation for Lisfranc fracture, displaying pronation on the injured side based on the Foot Posture Index-6 test, as well as 15 healthy subjects, participated in this study. Plantar pressure distribution measurements were conducted during barefoot walking for the healthy subjects. In the patient group, measurements were taken under two antipronation taping conditions (kinesio and rigid taping), as well as during barefoot walking. Results: Participants who received anatomical fixation after Lisfranc fracture exhibited significant alterations in plantar pressure distribution parameters on both the injured and uninjured sides, as compared to the control group. After the application of Kinesio Taping to the injured side, there was no significant change observed in the plantar pressure distribution values (p > 0.05). The analysis of the rigid taping on the injured side revealed statistically worse values in peak pressure of the hindfoot (p = 0.027) and maximum force of the midfoot and toes (p = 0.005 and p = 0.013, respectively) compared to the injured barefoot condition. Significance: Lisfranc fracture sequelae affected plantar pressure distribution on both injured and uninjured sides. Anti-pronation taping (kinesio and rigit), commonly used for foot conditions, did not lead to foot pressure distribution becoming more similar to that of the control group.